2016
DOI: 10.1016/j.mgene.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and ultra-rapid metabolizers with CYP2C19 *17 polymorphism do not respond to standard therapy with proton pump inhibitors

Abstract: Introduction and objectivePolymorphisms in genes encoding drug metabolizing enzymes may lead to varied enzyme activity and inter-individual variability in drug efficacy and/or toxicity. Since CYP2C19 and CYP3A4 genes code for enzymes involved in metabolizing wide variety of drugs including proton pump inhibitors, we sought to identify polymorphisms in these genes in order to study their impact on drug metabolism in subjects.MethodsDNA was isolated from healthy individuals including tribals and genotyped for 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
2
19
0
3
Order By: Relevance
“…Os portadores da variante CYP2C19*17 foram denominados metabolizadores ultrarrápidos. 83 A raça parece ser outro fator com papel importante nesse cenário. Cresci et al 84 compararam o efeito do polimorfismo do CYP2C19 sobre eventos CVs adversos entre pacientes com infarto agudo do miocárdio em caucasianos e afroamericanos tratados com clopidogrel.…”
Section: Clopidogrelunclassified
“…Os portadores da variante CYP2C19*17 foram denominados metabolizadores ultrarrápidos. 83 A raça parece ser outro fator com papel importante nesse cenário. Cresci et al 84 compararam o efeito do polimorfismo do CYP2C19 sobre eventos CVs adversos entre pacientes com infarto agudo do miocárdio em caucasianos e afroamericanos tratados com clopidogrel.…”
Section: Clopidogrelunclassified
“…9 The distribution of CYP2C19 phenotypes was divided into 4 phenotypes: extensive metabolizers (EM), intermediate metabolizers, ultra-rapid metabolizers, and poor metabolizers. 10 CYP2C19 is responsible for > 80% of the metabolism of omeprazole, lansoprazole, and pantoprazole metabolism. 11 Esomeprazole, the S-isomer of omeprazole, is metabolized to a less extent by CYP2C19 than omeprazole.…”
Section: Introductionmentioning
confidence: 99%
“…While heterozygote individuals with one normal activity allele and one variant allele associated with increased activity (*17), CYP2C19 *1/*17 are considered extensive metabolizers (EM) although this continues to be under study . Clinical implication of CYP2C19 *17/*17 polymorphism relies on the following: If PPIs are quickly metabolized, standard PPIs dose fails to adequately suppress acid secretion, and H pylori eradication therapy will be less effective if the microorganism is sensitive to antibiotics . A recent work in Colombia to eradicate H pylori , using triple therapy with clarithromycin or levofloxacin combined with amoxicillin, reported that although the organism was sensitive to these antibiotics, there was variability with achieved eradication .…”
Section: Introductionmentioning
confidence: 99%
“…21,23 Clinical implication of CYP2C19*17/*17 polymorphism relies on the following: If PPIs are quickly metabolized, standard PPIs dose fails to adequately suppress acid secretion, and H pylori eradication therapy will be less effective if the microorganism is sensitive to antibiotics. 19,21,24,25 A recent work in Colombia to eradicate H pylori, using triple therapy with clarithromycin or levofloxacin combined with amoxicillin, reported that although the organism was sensitive to these antibiotics, there was variability with achieved eradication. 26 These results may suggest the possibility that additional factors, different from antimicrobial resistance, can influence treatment effectiveness in our population.…”
mentioning
confidence: 99%